2020
DOI: 10.3389/fnut.2020.580780
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Deficiency in the Early-Life Periods Alters a Diversity of the Colonic Mucosal Microbiota in Rats

Abstract: Vitamin A deficiency (VAD) remains a public health issue worldwide, affecting pregnant women and children. The early-life microbiota is a potentially effective intervention target for modulating immune and metabolic development of the host. This paper investigates the effects of VAD during different life periods on the structure of the colonic mucosa microbiota in adolescent rats. The results showed that the concentrations of serum retinol were > ~1.05 μmol/L in maternal VA normal (VAN)rats and <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Bacteroidetes and Firmicutes fundamentally include gram‐negative bacteria, apart from gram‐positive Firmicutes microorganisms (Greenhill, 2015 ; Indiani et al, 2018 ), and some polysaccharide degrading enzymes kinds are generated by Bacteroidetes phylum, whereas there was fewer current number of microbes with polysaccharide degradation capacity within Firmicutes phylum (Allaband et al, 2019 ; Johnson et al, 2017 ). In terms of ecological imbalance, VAD brought about disproportionate abundances of Firmicutes and Bacteroidetes within the intestines, fitting other experiment researchers' results (Chen et al, 2020 ; Liu et al, 2016 ). In the above data segregation, various conditional pathogenic bacteria are shown to occur within mice with different VA levels.…”
Section: Discussionsupporting
confidence: 85%
“…Bacteroidetes and Firmicutes fundamentally include gram‐negative bacteria, apart from gram‐positive Firmicutes microorganisms (Greenhill, 2015 ; Indiani et al, 2018 ), and some polysaccharide degrading enzymes kinds are generated by Bacteroidetes phylum, whereas there was fewer current number of microbes with polysaccharide degradation capacity within Firmicutes phylum (Allaband et al, 2019 ; Johnson et al, 2017 ). In terms of ecological imbalance, VAD brought about disproportionate abundances of Firmicutes and Bacteroidetes within the intestines, fitting other experiment researchers' results (Chen et al, 2020 ; Liu et al, 2016 ). In the above data segregation, various conditional pathogenic bacteria are shown to occur within mice with different VA levels.…”
Section: Discussionsupporting
confidence: 85%
“…Emerging evidence shows that VAD in the different life stages could impair gut microbiota homeostasis, leading to the imbalance of Firmicutes and Bacteroidetes in rat colonic mucosal microbiota ( Chen et al, 2020 ). Amit-Romach et al (2009) illustrated that VAD could change the composition of gut microbiota and damage the integrity of the gastrointestinal mucosal barrier by reducing the abundance of Lactobacillus and the total bacterial count in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin supplementation promotes intestinal beneficial bacteria, which improves the performance and quality of egg production in aged hens ( Gan et al, 2020a ). Several studies report that vitamin A and D deficiency alters the microbiota diversity and Firmicutes / Bacteroides ratio, thereby affecting host immunity and metabolic ( Chen et al, 2020 ; Singh et al, 2022 ). Evidence has demonstrated that Vitamin C addition enhances the shape of intestinal villi, boosts the diversity and richness of the microorganisms in the cecal, and reduces Bacteroidetes/Firmicutes ratio and Enterobacteriaceae .…”
Section: Discussionmentioning
confidence: 99%